Plummer Vinson Syndrome: A Rare Syndrome in Male with Review of the Literature - Priyadarshini Karthikeyan; Nalini Aswath; Ramesh Kumaresan (Case Reports in Dentistry)
Introduction. Plummer Vinson syndrome also known as Paterson Brown-Kelly syndrome is a syndrome associated with the triad of symptoms comprising microcytic hypochromic anemia, oesophageal strictures, and dysphagia. PVS is commonly found in women of middle age especially in the fourth and fifth decade of life and is rarely reported in males. Case Report. The authors report a case of 43-year-old male patient who presented with the classic symptoms of Plummer Vinson syndrome. Conclusion. Dentists have to be familiar with symptoms of PVS and a thorough clinical examination of the patient is necessary for early diagnosis and treatment. As PVS is a precancerous condition with high malignant potential, early diagnosis is of utmost importance for better prognosis. Clinical Significance. Mutual interaction of systemic and oral health has largely been underestimated by many patients in the developing countries and hence this report includes a note on importance of adequate medical history taking and its relevance to the dental health and treatment.